Anthropometric parameters in patients with ischemic myocardial dilation and CTLA4 rs231775 polymorphisms - Oksana O. Kuznetsova; Svetlana Yu. Nikulina; Anna A. Chernova; Vladimir N. Maximov (КардиоСоматика)
BACKGROUND: Ischemic myocardial dilation (IMD) develops as a result of coronary artery disease and may lead to heart failure with significantly reduced cardiac contractility. Previously we identified genetic factors associated with the risk of developing IMD. We found no data in available sources on the association between anthropometric characteristics and IMD.